Comparison of antimicrobial activities and resistance mechanisms of eravacycline and tigecycline against clinical Acinetobacter baumannii isolates in China - Chen, Xiandi; Li, Yitan; Lin, Yingzhuo; Guo, Yingyi; He, Guohua; Wang, Xiaohu; Wang, Mingzhen; Xu, Jianbo; Song, Mingdong; Tan, Xixi; Zhuo, Chao; Lin, Zhiwei (Frontiers in Microbiology, 2024)
Tigecycline (TGC) is currently used to treat carbapenem-resistant Acinetobacter baumannii (CRAB) infections, while eravacycline (ERV), a new-generation tetracycline, holds promise as a novel therapeutic option for these infections. However, differences in resistance mechanism between ERV and TGC against A. baumannii remain unclear. This study sought to compare characteristics and mechanisms of ERV and TGC resistance among clinical A. baumannii isolates. A total of 492 isolates, including 253 CRAB and 239 carbapenem-sensitive A. baumannii (CSAB) isolates, were collected from hospitalized patients in China. MICs of ERV and TGC against A. baumannii were determined by broth microdilution. Genetic mutations and expressions in resistant strains were examined by PCR and qPCR, respectively. In vitro recombination experiments were used to verify the resistance mechanism of ERV and TGC in A. baumannii. MIC90 of ERV in CRAB and CSAB isolates were lower than those of TGC. A total of 24 strains resistant to ERV and/or TGC were categorized into three groups: only ERV-resistant (n = 2), both ERV-and TGC-resistant (n = 7), and only TGC-resistant (n = 15). ST208 (75%, n = 18) was a major clone that has disseminated in all three groups. The ISAba1 insertion in adeS was identified in 66.7% (6/9) of strains in the only ERV-resistant and both ERV-and TGC-resistant groups, while the ISAba1 insertion in adeN was found in 53.3% (8/15) of strains in the only TGCresistant group. The adeABC and adeRS expressions were significantly increased in the only ERVresistant and both ERV-and TGC-resistant groups, while the adeABC and adeIJK expressions were significantly increased and adeN was significantly decreased in the only TGC-resistant group. Expression of adeS with ISAba1 insertion in ERV-and TGC-sensitive strains significantly increased the ERV and TGC MICs and upregulated adeABC and adeRS expressions. Complementation of the wildtype adeN in TGC-resistant strains with ISAba1 insertion in adeN restored TGC sensitivity and significantly downregulated adeIJK expression. In conclusion, our data illustrates that ERV is more effective against A. baumannii clinical isolates than TGC. ERV resistance is correlated with ISAba1 insertion in adeS, while TGC resistance is associated with the ISAba1 insertion in adeN or adeS in A. baumannii.